Enhancing Nutritional Quality of Unleavened Wheat Flatbread Using Oyster Mushroom flour: Elevating Wheat Flatbread’s Nutritional Profile with Mushroom Flour - Dhillon, Gurpreet Kaur; Mahajan, Monika (Mushroom Research, 2023)
Whole wheat meal was supplemented with oyster mushroom flour (OMF) to create a healthier version of unleavened flatbread. Oyster mushrooms were sundried and ground into flour to supplement at 5, 10, 15 and 20% in whole wheat meal. The addition of OMF significantly increased the water absorption (%) of dough, while dough handling was smooth and non-sticky. Prepared flatbreads showed full puffing in control, 5, 10 and 15% inclusion levels, while partial puffing was observed in flatbread containing 20% OMF. OMF significantly improved the flatbread’s crude protein, crude fibre, and ash content. Moreover, compared to the control, a significant increase was observed in the in vitro protein digestibility (IVPD) of supplemented flatbreads. The sensory evaluation suggested that up to 15% OMF level in flatbread did not alter the sensory attributes and was acceptable and comparable with the wheat flatbread. Further, the trainees appreciated the dissemination of the technology using the household processing technique as it provides an economical means to add mushroom protein of high biological value to staple food.